2018
DOI: 10.3390/min8030091
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Arsenate Adsorption onto Alumina Surfaces

Abstract: Atomistic modeling of mineral-water interfaces offers a way of confirming (or refuting) experimental information about structure and reactivity. Molecular-level understanding, such as orbital-based descriptions of bonding, can be developed from charge density and electronic structure analysis. First-principles calculations can be used to identify weaknesses in empirical models. This provides direction on how to propose more robust representations of systems of increasing size that accurately represent the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
0
19
0
1
Order By: Relevance
“…NLOP had a significant correlation with Fe (R = 0.933, p < 0.01, n = 65). This showed that NLOP was easily an effective carrier of Fe [72]. There were significant correlations between Po fractions and TP, Pi, and Po.…”
Section: Relationships Between Po Fractions and Physiochemical Featuresmentioning
confidence: 78%
“…NLOP had a significant correlation with Fe (R = 0.933, p < 0.01, n = 65). This showed that NLOP was easily an effective carrier of Fe [72]. There were significant correlations between Po fractions and TP, Pi, and Po.…”
Section: Relationships Between Po Fractions and Physiochemical Featuresmentioning
confidence: 78%
“…CO 2 capture is one of the most cost-effective and practical methods to mitigate global warming effects. Conventional CO 2 capture technologies mainly include absorption, adsorption and membrane separation [1][2][3]. The use of traditional adsorbents such as activated carbon (AC), silica and zeolites for CO 2 separation has grown steadily, primarily because adsorption is energy efficient with fast adsorption/desorption rates and a reduction of corrosion [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the chosen functional is supported by a benchmark study of water over alumina where both adsorption energy and structural parameters were found to be in agreement with both MP2 methods and hybrid functionals like B3LYP and HSE06 40 . Furthermore, the functional have been extensively used in the community when computing adsorption energies(PBE, PW91) [41][42][43][44] .…”
Section: Computational Detailsmentioning
confidence: 99%